The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1743-422x-10-229
|View full text |Cite
|
Sign up to set email alerts
|

Active vaccination with vaccinia virus A33 protects mice against lethal vaccinia and ectromelia viruses but not against cowpoxvirus; elucidation of the specific adaptive immune response

Abstract: Vaccinia virus protein A33 (A33VACV) plays an important role in protection against orthopoxviruses, and hence is included in experimental multi-subunit smallpox vaccines. In this study we show that single-dose vaccination with recombinant Sindbis virus expressing A33VACV, is sufficient to protect mice against lethal challenge with vaccinia virus WR (VACV-WR) and ectromelia virus (ECTV) but not against cowpox virus (CPXV), a closely related orthopoxvirus. Moreover, a subunit vaccine based on the cowpox virus A3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
(62 reference statements)
0
18
1
2
Order By: Relevance
“…All efforts were made to minimize animal suffering. The end-points were weight loss (25% of the initial weight in the infected untreated groups and 40% in the treated groups) and/or inability to respond to the righting reflex [39] . Animals that reached these predetermined end-points were humanely sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…All efforts were made to minimize animal suffering. The end-points were weight loss (25% of the initial weight in the infected untreated groups and 40% in the treated groups) and/or inability to respond to the righting reflex [39] . Animals that reached these predetermined end-points were humanely sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…The data we obtained using single alanine scanning mutagenesis within the A27D7 antibody epitope may explain why a previous study observed that vaccination with recombinant Sindbis virus expressing A33 VACV conferred protection against ECTV but not CPXV [ 31 ]. In this case, vaccination might not have elicited anti-A33 antibodies that could bind the Gln173Arg variation found in cowpox.…”
Section: Discussionmentioning
confidence: 91%
“…A former study showed that VACV-A33 vaccination protected mice against ECTV but interestingly not against CPXV-Br [ 31 ]. The reason for the lack of protection remains unclear, because VACV is more closely related to CPXV-Br than to ECTV ( S4 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ectromelia virus (an othropoxvirus that causes mousepox) is lethal in B cell deficient mice despite mounting a CD8 T cell response, while passive transfer of immune serum allows such mice to clear an established infection and fully recover (45). The expectation that antibodies to VACV membrane proteins could mediate protection has been confirmed by virus neutralizing studies in vitro (39, 46-62), and several purified membrane proteins, including WR101/H3L (39), WR187/B5R (51), WR156/A33R (51, 63, 64), WR151/A28L (59), WR132/A13L (60), and WR150/A27L (65) have been shown to protect animals against challenge in vivo . Proteome-wide screening by microarray for antibody targets in sera confirmed the response is heavily skewed towards recognition of virion-associated targets (29, 39, 41, 66).…”
Section: Discussionmentioning
confidence: 92%